A Comprehensive Review of Molecular Mechanisms for Biotic and Abiotic Stress Adaptation in Roses - Salih , Rusul Mahdy; Alzubaidi, Mohaiman Khalifa Qahar; Hamad , Sara Salam (American Journal of Biology and Natural Sciences, 2026)
The agricultural sector worldwide faces an unparalleled challenge due to the growth of the population and the increasing impact of climate change. Global food production needs to increase by an estimated 60–110% by 2050 for food security, given a world population of about 9-10 billion. [1] This increasing demand is even aggravated by the rise in abiotic stress such as drought, salinity and extremes of temperature, which remain to be serious constraints to agricultural productivity and result in significant loss of arable land [2].